Taking stock of labour trafficking in the Netherlands: Bilans zjawiska handlu ludźmi do pracy przymusowej w Holandii (Archives of Criminology, 2023)
In the Netherlands, labour trafficking was criminalised as human trafficking in 2005. Since then, criminal investigations into labour trafficking have slowly taken off. Building on a content analysis of files and reports from the labour inspectorate, this paper contributes to the currently limited body of knowledge on the nature of labour trafficking. It does so by focussing on scholarly debates about the nature of the crime and its relation to labour migration. Based on the analysis, it is argued that the bulk of labour trafficking should be understood as a by-product of labour migration, and that labour trafficking often arises from the economic opportunistic motives of businesses and only occasionally occurs in criminal environments. In addition, the paper adds to our understanding of the prosecution of human trafficking by analysing why so many labour trafficking cases in the Netherlands have not resulted in a conviction. Building on a qualitative analysis of case law, it is shown that a major problem in getting suspects convicted is that the human rights threshold against which cases of labour trafficking are tested is often not surpassed, as the abuses in the labour market are often deemed not excessive enough to qualify as human trafficking.